The Magnetic Memory of Titan's Ionized Atmosphere - Bertucci, Cesar (2008)
After 3 years and 31 close flybys of Titan by the Cassini Orbiter, Titan was finally observed in the shocked solar wind, outside of Saturn’s magnetosphere. These observations revealed that Titan’s flow-induced magnetosphere was populated by “fossil” fields originating from Saturn, to which the satellite was exposed before its excursion through the magnetopause. In addition, strong magnetic shear observed at the edge of Titan's induced magnetosphere suggests that reconnection may have been involved in the replacement of the fossil fields by the interplanetary magnetic field.